2017
DOI: 10.12965/jer.1734914.457
|View full text |Cite|
|
Sign up to set email alerts
|

Interval and continuous aerobic exercise training similarly increase cardiac function and autonomic modulation in infarcted mice

Abstract: The present study aimed to compare the effects of moderate-intensity continuous and high-intensity interval exercise training (ET) on exercise tolerance, cardiac morphometry and function, hemodynamic, and cardiac autonomic modulation in myocardial infarcted mice. Wild-type mice (WT) were divided into four groups: sedentary WT (S); WT myocardium infarction sedentary (IS); WT myocardium infarction underwent to moderate-intensity continuous ET (MICT), and WT myocardium infarction underwent to high-intensity inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…The analysis in the PI and SAP frequency domain was performed using the Fast Fourier Transform to obtain the power spectrum of the low frequency (LF, 0.40-1.50 Hz) and high frequency bands (HF, 1.50-5.0 Hz -only for the PI). The bands were presented in nor malized units [28,32,33]. In addition, the BF/AF ratio (sympatho vagal balance) was calculated.…”
Section: Cardiovascular Autonomic Modulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis in the PI and SAP frequency domain was performed using the Fast Fourier Transform to obtain the power spectrum of the low frequency (LF, 0.40-1.50 Hz) and high frequency bands (HF, 1.50-5.0 Hz -only for the PI). The bands were presented in nor malized units [28,32,33]. In addition, the BF/AF ratio (sympatho vagal balance) was calculated.…”
Section: Cardiovascular Autonomic Modulationmentioning
confidence: 99%
“…The animals were anesthetized (0.5 % -2 % isoflurane, 98 % O 2, 1.5 L/ min) [28], and a Tygon polyethylene cannula was implanted in the carotid artery for direct AP measurement, and jugular vein for drug administration Tramadol 60 mg/kg (i.p.) was administered every 12 hours for analgesic effects [12,13,28].…”
Section: Arterial Pressure Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…97 Given the beneficial physiological cardiac adaptions of HIIT training, several investigations have studied the potential benefits of HIIT in animal models of cardiac disease states. When performed after MI in rodent models, HIIT has been shown to improve exercise capacity, [141][142][143][144] attenuate ventricular and cellular hypertrophy, 39 restore FS, 39,[144][145][146][147] ejection fraction, 95,143,[147][148][149] and diastolic dysfunction, 94,141,147 as well as normalize cardiomyocyte Ca 2+ handling and sensitivity, 39,142,144,146 alleviate mitochondrial dysfunction, 145 preserve endothelial function, 95 increase angiogenesis, 94 and reduce collagen accumulation. 94 In models of diet-induced obesity, low exercise capacity, and diabetic cardiomyopathy, HIIT has conferred therapeutic improvements in VO 2max 53,150,151 systolic and diastolic function, 150,151 cardiac mechanoenergetics, 150,152 and cardiac fibrosis, 150,151 as well as alterations of cholesterol, 53 insulin resistance, 151 and substrate utilization.…”
Section: Treadmill Training: High-intensity Interval Trainingmentioning
confidence: 99%
“…In addition to exercise volume (intensity and duration) and type of exercise, other factors such as age, gender, and race also play a role in the development of certain ECG patterns [2]. Cal Abad (2017) showed that continuous and interval training aerobic exercise similarly increases cardiac function and autonomic modulation in mice with myocardial infarction [11], but they did not mention how exercise do affect the ECG of the subjects. Most previous studies that have examined the effect of exercise on ECG indicators are retrospective, causal-comparative (post-event) type [4][5][6][7][8]10], and few experimental and prospective studies have been conducted in this area [9].…”
mentioning
confidence: 99%